IMPLICATIONS OF Acanthus ilicifolius LEAF EXTRACT UTILIZATION TO INHIBIT Candida albicans GROWTH TO SUPPORT MANGROVE CONSERVATION - Maulinna Kusumo Wardhani; Askur Rahman (Jurnal Teknologi Perikanan dan Kelautan)
Acanthus ilicifolius, a mangrove species with known therapeutic material, was investigated for its ability to inhibit the growth of Candida albicans. This study aimed to analyze the potential inhibitory effect of A. ilicifolius leaf extracts on the growth of Candida albicans yeast. The method used in this study was a completely randomized laboratory experimental design. A. ilicifolius leaf and C. albicans yeast samples were collected from the mangrove areas in Socah District (Bangkalan Regency) and Paiton District (Probolinggo Regency). Leaf samples were extracted using the 99.98% methanol maceration method, followed by phytochemical analysis and an inhibition test. Qualitative phytochemical analysis of A. ilicifolius showed the presence of active compounds, alkaloids, flavonoids, steroids/terpenoids, tannins, and phenols, while saponins were absent. Quantitative tests showed flavonoids as the dominant active compound (162.79 ppm). The A. ilicifolius leaf extract exhibited weak to moderate inhibitory effects against C. albicans, with each concentration demonstrating significantly different effects. However, there was no statistically significant difference in the active compound content between the two locations. This study highlights the pharmacological potential of A. ilicifolius as a plant-based anti-yeast agent for alternative therapies and underscores the importance of mangrove conservation.